2021
DOI: 10.1002/fuce.202000168
|View full text |Cite
|
Sign up to set email alerts
|

Anode‐supported solid oxide fuel cells with multilayer LSC/CGO/LSC cathode

Abstract: The multilayer La 0.6 Sr 0.4 CoO 3 /Ce 0.9 Gd 0.1 O 2 /La 0.6 Sr 0.4 CoO 3 (LSC/CGO/LSC) thin film cathode of the solid oxide fuel cell (SOFC) with the different thickness of the LSC and CGO layers are obtained by magnetron sputtering. Cathodes are deposited onto the NiO/8YSZ anode-supported 8YSZ/CGO bilayer electrolyte.The influence of the deposited multilayer cathode on the SOFC performance is investigated in the temperature range between 800 and 600 • C. It is shown that the thin-film multilayer cathode all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 33 publications
0
6
2
Order By: Relevance
“…The polarization impedances of LSC, LSC9, LSC8, LSC7, LSC6, and LSC5 at 600°C and 650°C in Figure 6B, which account for 0.1714, 0.1291, 0.1071, 0.0981, 0.0877, and 0.0801 Ω cm 2 , respectively, at 650°C. These results are far lower than the multilayer cathode structure reported by Solovyev et al 33 …”
Section: Resultscontrasting
confidence: 63%
See 2 more Smart Citations
“…The polarization impedances of LSC, LSC9, LSC8, LSC7, LSC6, and LSC5 at 600°C and 650°C in Figure 6B, which account for 0.1714, 0.1291, 0.1071, 0.0981, 0.0877, and 0.0801 Ω cm 2 , respectively, at 650°C. These results are far lower than the multilayer cathode structure reported by Solovyev et al 33 …”
Section: Resultscontrasting
confidence: 63%
“…Moreover, uniformly distributed GDC nanoparticles can significantly prolong the TPBs at the oxygen electrode reaction interface, thus reducing the R p of the oxygen electrode. The polarization impedances of LSC, LSC9, LSC8, LSC7, LSC6, and LSC5 at 600 • C and 650 • C in Figure 6B, which account for 0.1714, 0.1291, 0.1071, 0.0981, 0.0877, and 0.0801 Ω cm 2 , respectively, at 650 • C. These results are far lower than the multilayer cathode structure reported by Solovyev et al 33 To further study, the performances of button cells of LSC-GDC composite cathode with various mass proportions were tested. ) and air were used as fuel and oxidant, respectively, during the discharge, with a discharge current of 600 mA cm −2 at 650 • C. The reason why the voltage rises and falls may be that each functional layer forms a good interface and Ni coarsening.…”
Section: Resultscontrasting
confidence: 53%
See 1 more Smart Citation
“…7b, the cell with the LSC50 cathode show the best performance, reaching a peak power density of 302, 585, 1013, 1535 and 1963 mW cm -2 at 600, 650, 700, 750 and 800 ℃, respectively. A.A. Solovyev reported the maximum power density of 2430, 1170, and 290 mW cm -2 is obtained respectively at 800, 700, and 600 ℃ for the SOFCs with multilayer LSC/CGO/LSC cathode [36]. But the multilayer cathode working in high temperature is not the tendency for the…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 98%
“…Previous studies have shown that mixing perovskites such as LSC with an excellent ionic conducting material such as gadoliniadoped ceria (GDC) into a composite structure leads to significant improvements in performance. A.A. Solovyev et al reported that anode-supported solid oxide fuel cells with multilayer LSC/CGO/LSC cathode of 50/50/50 nm thick obtained high prosperity [36]. The LSC-GDC electrode also shows good performance when used as the cathode in solid oxide electrolysis cells [37].…”
Section: Introductionmentioning
confidence: 99%